Modernización y política artística: el Centro Nacional de Exposiciones entre 1983 y 1989 - Ait Moreno, Isaac (Anales de Historia del Arte, 2007)
Nowadays, exhibition spaces consecrated to new tendencies in art –museums, art centers, biennials, art fairs…– are developing in Spain. Nonetheless, contemporary art began to be largely shown at this country in the eighties, due to the contribution of public and private institutions that renovated art exhibition scene inherited from Franco’s regime. My article talks about the trajectory of one of the most outstanding public institutions involved in such renovation, the Centro Nacional de Exposiciones (CNE), a government entity within the Ministry of Culture which set up a whole series of major shows from 1983 to 1989. This action meant a remarkable and polemical episode in the last Spanish arts policy. Available data about CNE allows to prove that although its role in the promotion of contemporary art was praiseworthy, its program lacked the necessary coherence and unity.